ANALYSIS OF COMPANY VALUE IN THE AUTOMOTIVE AND AUTOMOTIVE COMPONENTS SUB-SECTOR IN INDONESIA STOCK EXCHANGE - Agatha, Rizky Keyla; Suwaidi, Rahman Amrullah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of company growth and liquidity on company value, as well as the influence of capital structure in moderating the relationship between company growth and liquidity to company value in the automotive sub-sector and automotive components listed on the IDX in 2019-2023. Samples in this finding were 45, taken using the purposive sampling method. This study uses secondary data in the form of the company's annual financial statements which are analyzed using Moderated Regression Analysis. The results of this study indicate that company growth does not contribute to company value, liquidity contributes to company value, and capital structure is able to moderate the relationship between company growth and liquidity to company value.